Studies on the related Neotropical genera Acrogymnia Malaise and Dacrogymnia, n. gen. (Hymenoptera: Argidae) - Smith, David R.; Malagón-Aldana, Leonardo A. (Zootaxa, 2020)
Twenty species of Acrogymnia Malaise and five species of Dacrogymnia Smith & Malagón-Aldana, n. gen., both exclusively Neotropical genera, are treated. Acrogymnia occurs from Costa Rica south to Bolivia and southeastern Brazil and Dacrogymnia from southern Colombia to Argentina. The following species are included: Acrogymnia alagoas Smith, n. sp., A. blanki Smith, n. sp., A. brevis Smith, n. sp., A. chapada Smith, n. sp., A. clypea Smith, n. sp., A coxalis (Konow, 1906), A. deulufeuti Smith, n. sp., A. diamantinensis Malaise, 1955, A. fascia Smith, n. sp., A. krylita Smith, n. sp., A. listoni Smith, n. sp., A. lopesi Malaise, 1949, A. palama Smith, 1992, A. pauxilla (Konow, 1906), A. pereirai Smith & Malagón-Aldana, n. sp., A. pulla Smith, n. sp., A. pusilla (Malaise, 1937), A. rufina Malaise,1949, A. scutimacula Malaise, 1941, A. transtillata (Konow, 1906), Dacrogymnia acella (Smith, 1992), n. comb., D. imbogea (Smith,1981), n. comb., D. australis Smith, n. sp., D. fernandezi Smith & Malagón-Aldana, n. sp., and D. taegeri Smith, n. sp. An identification key for species is provided; however, association of sexes in Acrogymnia is still uncertain for several species.